Modified bentonite in-situ polymerization type mineral flocculant and preparation method thereof
Through the preparation of modified bentonite in situ polymerized mineral flocculants, the problems of large flocculants and poor flocculation effect of small-particle minerals during ore dressing are solved, efficient flocculation and dehydration of small-particle minerals are achieved, and the recovery rate of phosphate ore is improved.
Patent Information
- Application Number
- CN202411545279.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-08-14
- Filing Date
- 2024-11-01
- Publication Date
- 2025-03-04
AI Technical Summary
During the ore dressing process, the flocculant used in the prior art is large, which has poor flocculation effect on small-particle minerals. Excessive polymers will lead to excessive moisture content of concentrates and increase the cost of use.
The modified bentonite in situ polymerization mineral flocculant is used to modify the bentonite by in situ polymerization of intercalated monomers to obtain a mineral flocculant with a special structure. The flocculant includes bentonite, intercalation agent, polymer monomer and initiator, and is prepared by ultrasonic dispersion, interlayer modification, pretreatment, intercalation, polymerization and drying grinding.
The better flocculation and dehydration effect of 5-20μm small-particle minerals is achieved, which improves the recovery rate of phosphate ores, and reduces the amount and cost of flocculant.
Smart Images

Figure CN119551781A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of mineral processing, and in particular to the technical field of flocculants for concentrating mineral slurries. Background Art
[0002] In the process of mineral beneficiation, gravity separation, flotation, magnetic separation and other methods are used according to the different physical and chemical properties of different minerals in the ore. In the flotation method, it is often necessary to concentrate the concentrate after flotation. In industrial production, a thickening tank is usually used for concentration, and flocculants are added to accelerate flocculation to improve the processing efficiency of the thickening tank.
[0003] Usually, the flocculant is a polymer, such as a mixture of one or more polymers such as polyacrylamide and polyaluminium chloride. In the prior art, if the amount of flocculant is too low, the flocculation effect on small-sized mineral particles is poor, especially for small-particle minerals at the micron level, which will slow down the flocculation speed, causing the thickening tank to become turbid and the concentrate to be lost; but if the amount of flocculant is increased, the excessive amount of polymer will cause difficulties in the subsequent vacuum filtration and dehydration process of the concentrate, resulting in too high a water content of the concentrate and an increase in the cost of using the flocculant.
[0004] Bentonite is mainly composed of montmorillonite, which is a hydrated aluminum silicate or aluminum silicate mineral. Its crystal structure belongs to the monoclinic system and is composed of structural unit layers and interlayer domains. It can undergo ion exchange, which makes bentonite have excellent catalytic and adsorption properties. By using the interlayer domains between the structural unit layers in bentonite as a reaction site and compounding it with polymers, bentonite with improved performance can be obtained, which has richer application scenarios. The preparation methods of polymer / bentonite nanocomposites mainly include intercalation polymerization and polymer intercalation. Among them, the intercalation polymerization method is a method of first intercalating monomers and then polymerizing the monomers in situ. After the intercalated monomers are dispersed in the interlayer domains of bentonite, an initiator is added to carry out a polymerization reaction to achieve a nanocomposite of polymer and bentonite.
[0005] The Chinese patent application number CN201810423119.8 discloses a method for preparing a composite flocculant, comprising the following steps: calcining and activating bentonite, and then intercalating to obtain intercalated modified bentonite; compounding magnesium aluminum silicate, silane coupling agent, and N-hydroxyethyl acrylate to obtain modified magnesium aluminum silicate; compounding modified magnesium aluminum silicate with silicon tetrachloride to obtain composite system A; adding intercalated modified bentonite to composite system A, and granulating to obtain a composite flocculant. The composite flocculant of the invention has good flocculation and turbidity removal effect. While making full use of the hydrolysis of silicon tetrachloride residual liquid, it improves the flocculation effect of the flocculant, and can show good flocculation effect at low dosage. In addition, the used composite flocculant can remove the condensed suspended matter after rinsing and put into use for the second time. However, the multi-layer structure of bentonite is not well utilized in this application. It is only to add more modified substances to cooperate with the flocculation effect of bentonite to better flocculate the suspended matter in the sewage. The process of flushing and recovering the flocculant does not mention whether it is applicable to flotation and mineral processing.
[0006] A Chinese patent application numbered CN201811134734.3 discloses a method for preparing a modified nanocellulose-bentonite composite material for the treatment of printing and dyeing wastewater. First, the cellulose from the sunflower seed shell is extracted by acid and alkali extraction, and the bentonite is modified by polyacrylamide so that part of the polyacrylamide structure is intercalated into the bentonite layer, which can provide more sites and surface pores, thereby improving the adsorption and the subsequent grafting reaction. The invention disperses cellulose in urea and then modifies the ammonium persulfate and polyacrylamide bentonite. The ammonium persulfate initiates the cellulose chain, and the hydroxyl grafted polyacrylamide on the initiated cellulose chain is successfully introduced through grafting polymerization for a certain period of time to obtain a composite material with dual effects of adsorption and flocculation. For the treatment of printing and dyeing wastewater, the composite material improves the decolorization performance while still maintaining excellent flocculation performance. However, the application proposes a method for modifying polymer intercalated bentonite. This method cannot effectively enter the interlayers of bentonite due to the narrow interlayer spacing of bentonite and the long molecular weight of the polymer. After the prepared polymer intercalated modified bentonite flocculant is dissolved in water, the long polymer chains exposed outside will wrap the bentonite, and then form agglomerates, affecting the adsorption effect of the bentonite.
[0007] The Chinese patent application number CN202110701825.6 discloses a polymer network modified bentonite and its in-situ polymerization preparation method. The preparation method is to dissolve the monomer and the cross-linking agent in water, add the bentonite, mix thoroughly, add the initiator, and then heat it to make the initiator produce free radicals, which are transferred to the carbon-carbon double bonds on the monomers, initiating the addition polymerization of the carbon-carbon double bonds, so that the carbon-carbon double bonds are converted into single bonds. Under the action of the cross-linking agent, the monomers are polymerized to obtain a polymer network, and the polymer network is in situ intercalated between the sheets of bentonite. The invention proposes to modify bentonite with a hydrophilic polymer to improve its hydrophilicity and barrier properties. The prepared polymer-modified bentonite overcomes the shortcomings of the original bentonite's poor barrier properties to acid, alkali, and salt solutions. Although the method of modifying bentonite by in-situ polymerization is adopted to arrange the polymer in an orderly manner between the layers of bentonite, the flocculation effect of the application is still unsatisfactory because the bentonite has not been modified.
[0008] The Chinese patent application number CN200910194347.3 discloses an organic-inorganic in-situ composite flocculant and its preparation method. The invention uses inorganic powder as a dispersed phase, adds acrylamide, an initiator and a solvent to form a mixed solution system, and performs in-situ polymerization at 40-70°C for 10-24 hours; the mass percentage of the inorganic powder in the solution system is 1-60%, the mass percentage of acrylamide in the solution system is 1-50%, and the mass ratio of the initiator to acrylamide is 0.5-2:100. The invention combines the advantages of organic and inorganic flocculants, gives full play to the flocculation effect of acrylamide and inorganic powder, and the organic-inorganic flocculant prepared by in-situ composite technology can make the decolorization rate of printing and dyeing wastewater reach more than 90%. For decolorization flocculation in the printing and dyeing industry, the minimum particle size can reach the nanometer level, but due to the different properties of lithium ion and bentonite, it is usually positively charged. The modification method mentioned in the application is not suitable for ore dressing flocculation containing more metal ions.
[0009] In summary, although the above patents propose that bentonite can be modified and used for mineral processing flocculation, except for simply utilizing the adsorption effect of bentonite, there is no technology indicating how to utilize the interlayer structure of bentonite to make it suitable for mineral processing flocculation, especially for small particles of minerals therein, to have good thickening and flocculation effects. Summary of the invention
[0010] In view of the problems that a large amount of flocculant is used and the flocculation effect on small-particle minerals is poor during the mineral processing, the first purpose of the present invention is to provide a modified bentonite in-situ polymerization mineral flocculant, which can achieve better flocculation and concentration for small-particle minerals with a particle size range of 5 to 20 μm and has a good dehydration effect after filtration.
[0011] The second object of the present invention is to provide a method for preparing a modified bentonite in-situ polymerization type mineral flocculant, wherein bentonite is modified based on the in-situ polymerization method of intercalation monomers to obtain a mineral flocculant with a special structure.
[0012] The technical solution adopted by the present invention to solve its technical problem is:
[0013] A modified bentonite in-situ polymerization type mineral flocculant, wherein the raw materials of the mineral flocculant include, by weight, 20-40 parts of bentonite, 6-40 parts of intercalation agent, 80-400 parts of polymer monomer, and 0.1-0.3 parts of initiator; wherein the polymer monomer accounts for 55%-95% of the total weight of the raw materials. The polymer monomer includes propylene, acrylamide or sodium acrylate; the initiator includes ammonium persulfate, azobisisobutyronitrile, azobisisobutyrizoline hydrochloride or tert-butyl hydroperoxide.
[0014] Furthermore, the polymer monomer is propylene, accounting for 55% to 75% of the total weight of the above raw materials; the polymer monomer is acrylamide, accounting for 60% to 90% of the total weight of the above raw materials; the polymer monomer is sodium acrylate, accounting for 75% to 95% of the total weight of the above raw materials.
[0015] Furthermore, the bentonite is sodium-based, the weight ratio of the sodium-based bentonite to the intercalant is 2-7:1, and the intercalant is a quaternary ammonium salt, accounting for 1%-10% of the total weight of the raw materials. Preferably, the quaternary ammonium salt is hexadecyltrimethylammonium bromide, accounting for 4%-10% of the total weight of the raw materials; the quaternary ammonium salt is methacryloyloxyethyltrimethylammonium chloride, accounting for 1%-6% of the total weight of the raw materials.
[0016] like Figure 1 As shown, the present invention utilizes the special lamellar structure of bentonite to insert a polymer to achieve the modification of bentonite, wherein the intercalant is selected as a quaternary ammonium salt, and the intercalant of the bentonite is first modified, and the intercalant of the quaternary ammonium structure enters the intercalation layer and reacts with the H in the bentonite. + Ion exchange occurs to obtain organic bentonite, which can expand the interlayer distance of bentonite, improve the interlayer microenvironment, and facilitate the subsequent organic monomer to enter the interlayer. When the bentonite is preferably sodium-based, the intercalation effect is better because sodium-based ion exchange is easier to occur than calcium-based, which can make the interlayer distance larger, which is conducive to the subsequent monomer to enter the interlayer. The addition ratio between the intercalation agent and the bentonite is controlled. If the addition ratio of the intercalation agent is too low, thorough ion exchange cannot be carried out, making it difficult for the monomer to enter the bentonite interlayer. If the addition ratio of the intercalation agent is too high, it will cause a waste of raw materials.
[0017] In the process of intercalation polymerization, the monomers are first dispersed and intercalated into the bentonite sheets, and then in-situ polymerization is carried out. The heat released during polymerization is used to overcome the Coulomb force between the sheets to peel them off, so that the sheets and the polymer matrix are compounded in the form of chemical bonds. Although the in-situ polymerization in the prior art can make acrylic acid and bentonite achieve a good compound, thereby improving the adsorption performance of bentonite, the acrylic acid socket bentonite prepared by this method contains more carboxyl groups on the long carbon chain, which is not very effective for the positively charged Cu 2+ It has a good attraction effect, but for mineral particles, the negatively charged mineral particles will be repelled, which is not conducive to the adsorption of mineral particles, and then leads to the deterioration of its adsorption effect on small particles of minerals in the mineral processing wastewater.
[0018] In summary, the adsorption effect of the flocculant of the present application on small-particle minerals is mainly due to the microporous structure of bentonite. The special structure of polymer intercalated bentonite is used to make the polymer occupy a part of the pores, and can be firmly combined with bentonite, so as to achieve a synergistic flocculation effect on the minerals; if the pores of bentonite are occupied too much, the adsorption effect of bentonite on small-particle mineral particles will be weakened. The role of the intercalation agent is to realize ion exchange and expand the interlayer spacing of bentonite. If the amount added is too little, the interlayer cannot be effectively expanded. If too much is added, it will cause a waste of raw materials. Therefore, the formula ratio between the preparation raw materials is selected to have a better flocculation effect on small mineral particles, especially mineral particles in the particle size range of 5 to 20 μm.
[0019] A method for preparing a modified bentonite in-situ polymerization type mineral flocculant comprises the following steps:
[0020] S1: Dispersion: Add acid and water to bentonite, adjust the pH to 3.5-4.5, and use ultrasonic dispersion with a frequency of 20kHz to obtain a suspension.
[0021] S2: Interlayer modification: Add an intercalating agent to the above suspension to obtain a flocculent precipitate.
[0022] S3: Pretreatment: The flocculent precipitate is washed, filtered, dried and ground to obtain an organic precursor with a particle size of 300 to 500 meshes.
[0023] S4: intercalation: adding a polymer monomer to the organic precursor to obtain an intercalation monomer, wherein the weight ratio of the organic precursor to the polymer monomer is 1:3 to 1:5.
[0024] S5: Polymerization: adding an initiator to the above intercalation monomer to initiate a polymerization reaction to obtain an intercalation polymer.
[0025] S6: Drying and grinding: The intercalated polymer is sequentially subjected to two steps of airflow drying and grinding to obtain a mineral flocculant with a particle size of 60 meshes.
[0026] The porous and loose structure of bentonite can be used to physically adsorb small particles. Traditional polymer mineral flocculants flocculate minerals in wastewater through charge adsorption and the "sweeping" effect of polymer bridge nets, but this type of mineral flocculant often has no obvious flocculation and sedimentation effect on electrically neutral and small particles of minerals. This application chooses to use monomer intercalation to modify bentonite, and then add an initiator to initiate polymerization, so that the polymer can effectively enter the bentonite interlayer and can swell well after being dissolved in water, thereby forming a better adsorption and flocculation effect on small mineral particles.
[0027] In S3 of the present application, after the intercalation agent is introduced, water washing, filtration, drying, grinding and other steps are carried out, which can effectively remove the metal ions in the bentonite, and the polymer monomer is added in a dry state. The treatment of S3 is particularly necessary for S4, which can facilitate the polymer monomer to enter the interlayer and further form a more stable flocculant structure.
[0028] In S4 of the present application, the weight ratio between the above-mentioned organic precursor and the above-mentioned polymer monomer is controlled to be 1:3 to 1:5. If the ratio exceeds this ratio and too little polymer monomer is added, some bentonite layers will not be able to be inserted with the polymer, and some bentonite will not be able to participate in the formation of in-situ polymerized mineral flocculants; if too much polymer monomer is added, the bentonite voids will be excessively occupied by the polymer, and the adsorption effect of the bentonite will be significantly weakened.
[0029] In S6 of the present application, the particle size of the flocculant is controlled at 60 meshes, and the specific surface area is appropriate, which can increase the dissolution rate of the mineral flocculant and avoid the formation of "fish eyes" when added, that is, the dissolution is too slow, resulting in part of the powder being wrapped and unable to swell.
[0030] Compared with the prior art, the embodiments of the present invention have at least the following beneficial effects:
[0031] The raw materials of the present invention are selected in a suitable ratio so that the polymer and bentonite can be firmly combined together, thereby achieving a synergistic flocculation effect on the mineral. The obtained bentonite-type mineral significantly increases the flocculation effect and dehydration effect of small-particle phosphate concentrate, thereby improving the recovery rate of phosphate rock. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is a schematic diagram of the structure of the polymer intercalated bentonite of the present application. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0034] It should be noted that, in the absence of conflict, the embodiments and features of the embodiments of the present invention can be combined with each other. The present invention will be further described in detail below in conjunction with specific embodiments.
[0035] All embodiments of the present invention are implemented by adopting the following technical scheme, and the specific steps include:
[0036] S1: Dispersion: Add acid and water to bentonite, adjust the pH to 3.5-4.5, and use ultrasonic dispersion with a frequency of 20kHz to obtain a suspension.
[0037] In this step, the bentonite is dispersed with acid and water to facilitate the subsequent intercalation agent to enter the interlayer domain. At the same time, the non-ionic Ca, Mg and other compounds in the bentonite under acidic conditions are converted into ions under acidic conditions to ensure that Ca 2+ Mg 2+ The effective dissolution of can further increase the interlayer distance of bentonite, which is convenient for the subsequent introduction of intercalation agents. + , and Na in bentonite + The ions are exchanged to facilitate the subsequent introduction of the intercalant; the frequency of the ultrasound is limited to achieve a better dispersion effect of the suspension, which is conducive to the reaction with the intercalant.
[0038] S2: Interlayer modification: adding an intercalating agent to the above suspension to obtain a flocculent precipitate, wherein the above intercalating agent is a quaternary ammonium salt.
[0039] In this step, the bentonite is modified by the intercalation agent to obtain a flocculent precipitate, that is, a modified bentonite, and the interlayers of the bentonite are modified by the intercalation agent. + Ion exchange occurs to obtain organic bentonite, the purpose of which is to expand the interlayer spacing of the bentonite, improve the interlayer microenvironment, and facilitate the subsequent polymer monomers to enter the interlayer.
[0040] S3: Pretreatment: The flocculent precipitate is washed, filtered, dried and ground to obtain an organic precursor with a particle size of 300 to 500 meshes.
[0041] In this step, an organic precursor for monomer intercalation is obtained. Water washing can reduce impurities in the organic bentonite and prevent subsequent impurities from affecting the polymerization rate, so that the polymerization rate can be controlled by the amount and type of initiator to obtain a polymer with a suitable molecular weight. The suction filtration and drying are for the purpose of adding the polymer monomer in a dry state, which is conducive to the monomer entering the bentonite interlayer, and for the convenience of subsequent grinding. The organic precursor after grinding controls the particle size, which can increase the specific surface area of the bentonite flocculant, thereby improving the adsorption and flocculation effect.
[0042] S4: intercalation: adding polymer monomers to the above organic precursors in a weight ratio of 1:3 to 1:5 to obtain intercalation monomers.
[0043] S5: Polymerization: adding an initiator to the above intercalation monomer to initiate a polymerization reaction to obtain an intercalation polymer.
[0044] S6: Drying and grinding: The intercalated polymer is sequentially subjected to two steps of airflow drying and grinding to obtain a mineral flocculant with a particle size of 60 meshes.
[0045] In some embodiments of the present invention, the intercalation agent includes hexadecyl trimethyl ammonium bromide and methacryloyloxyethyl trimethyl ammonium chloride. The selection of intercalation agents is provided to achieve a good intercalation modification effect. The cations in the quaternary ammonium salt can react with the H introduced into the bentonite. + Ion exchange occurs, and after the ion exchange, the long-chain alkyl group enters the interlayer of bentonite, acting as a surfactant, which is beneficial to the introduction of subsequent polymer monomers.
[0046] In some embodiments of the present invention, the polymer monomers include propylene, acrylamide or sodium acrylate. After the intercalation monomers are obtained, they contain C=C unsaturated dibasic organic matter, which can then undergo polymerization reaction under the condition of adding an initiator.
[0047] In some embodiments of the present invention, the initiator includes ammonium persulfate, azobisisobutyronitrile, azobisisobutyrizoline hydrochloride or tert-butyl hydroperoxide. The initiator is provided for the monomer to initiate the polymerization reaction to generate a polymer, so that the polymerization effect is better. The selection of these initiators can control the generation rate of free radicals, thereby controlling the polymerization rate of the polymerization reaction, and controlling the molecular weight of the product within a reasonable range.
[0048] Embodiments 1 to 5
[0049] Examples 1 to 5 of the present invention are all implemented according to the above technical solution, and the specific implementation conditions are shown in Table 1.
[0050] Comparative Example 1
[0051] Comparative Example 1 is substantially the same as the embodiment, except that polyacrylamide is used to directly intercalate the bentonite, rather than intercalating the polymer monomer and then polymerizing it in situ to obtain the polymer.
[0052] Comparative Examples 2 and 3 respectively selected commercially available mineral flocculants, wherein Comparative Example 2 mainly used bentonite, and in Comparative Example 3, the ratio of polyacrylamide to bentonite was 1:10.
[0053] The specific implementation conditions of different embodiments and comparative examples are summarized in Table 1:
[0054] Table 1 Implementation conditions of Examples 1 to 5 and Comparative Examples 1 to 3
[0055]
[0056]
[0057] Phosphate slurry (concentration of 21.5%) from a phosphate mine in Sichuan Province was taken and flocculation tests were carried out using the flocculants of Comparative Examples 1 to 3 and Examples 1 to 5, respectively.
[0058] The experiment was conducted using a 1000ml stoppered measuring cylinder. After adding 1000ml of phosphate slurry, 0.65ml of different flocculant solutions (diluted to 0.2‰ solution) were added respectively. After shaking well, the timing was started, the reading at the flocculation layer was recorded, and the turbidity of the upper clear liquid was tested with a turbidity meter. The test results are shown in Table 2:
[0059] Table 2 Implementation of Examples 1 to 5 and Comparative Examples 1 to 3
[0060]
[0061] In summary, it can be seen from the volume of the lower flocculant after 10 minutes and the turbidity of the supernatant that the flocculant prepared in the present application has better adsorption and flocculation effects on small-particle minerals, and the dehydration effect is better than that of commercially available products, and can be well applied to mineral processing and recovery.
[0062] The embodiments described above are part of the embodiments of the present invention, rather than all of the embodiments. The detailed description of the embodiments of the present invention is not intended to limit the scope of the application claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
Claims
1. A modified bentonite in-situ polymerization type mineral flocculant, characterized in that: In terms of weight, the raw materials of the flocculant include: 20-40 parts of bentonite, 6-40 parts of intercalating agent, 80-400 parts of polymer monomer, and 0.1-0.3 parts of initiator; wherein the polymer monomer accounts for 55%-95% of the total weight of the raw materials.
2. A modified bentonite in-situ polymerization type mineral flocculant according to claim 1, characterized in that: The polymer monomer is propylene, and the propylene accounts for 55% to 75% of the total weight of the raw material.
3. The modified bentonite in-situ polymerization type mineral flocculant according to claim 1, characterized in that: The polymer monomer is acrylamide, and the acrylamide accounts for 60% to 90% of the total weight of the raw materials.
4. The modified bentonite in-situ polymerization type mineral flocculant according to claim 1, characterized in that: The polymer monomer is sodium acrylate, and the sodium acrylate accounts for 75% to 95% of the total weight of the raw materials.
5. The modified bentonite in-situ polymerization type mineral flocculant according to claim 1, characterized in that: The intercalant is a quaternary ammonium salt, the weight ratio of the bentonite to the quaternary ammonium salt is 2-7:1, and the quaternary ammonium salt accounts for 1%-10% of the total weight of the raw materials.
6. The modified bentonite in-situ polymerization type mineral flocculant according to claim 5, characterized in that: The quaternary ammonium salt is hexadecyltrimethylammonium bromide, which accounts for 4% to 10% of the total weight of the raw materials.
7. The modified bentonite in-situ polymerization type mineral flocculant according to claim 5, characterized in that: The quaternary ammonium salt is methacryloyloxyethyl trimethyl ammonium chloride, which accounts for 1% to 6% of the total weight of the raw materials.
8. The modified bentonite in-situ polymerization type mineral flocculant according to claim 1, characterized in that: The bentonite is sodium based.
9. The modified bentonite in-situ polymerization type mineral flocculant according to claim 1, characterized in that: The initiator includes ammonium persulfate, azobisisobutyronitrile, azobisisobutyrizoline hydrochloride or tert-butyl hydroperoxide.
10. A method for preparing the modified bentonite in-situ polymerization type mineral flocculant according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1: Dispersion: Add acid and water to bentonite, adjust the pH to 3.5-4.5, and use ultrasonic dispersion with a frequency of 20kHz to obtain a suspension; S2: interlayer modification: adding an intercalation agent to the suspension to obtain a flocculent precipitate; S3: Pretreatment: washing, filtering, drying and grinding the flocculent precipitate to obtain an organic precursor with a particle size of 300-500 mesh; S4: intercalation: adding a polymer monomer to the organic precursor to obtain an intercalation monomer; S5: polymerization: adding an initiator to the intercalation monomer to initiate a polymerization reaction to obtain an intercalation polymer; S6: Drying and grinding: The intercalated polymer is sequentially subjected to two steps of airflow drying and grinding to obtain a mineral flocculant with a particle size of 60 meshes.
11. The method for preparing a modified bentonite in-situ polymerization type mineral flocculant according to claim 10, characterized in that: In the step S4, the ratio of the organic precursor to the polymer monomer is 1:3 to 1:5 by weight.
Citation Information
Patent Citations
Organic-inorganic in-situ composite flocculant and preparation method thereof
CN101717141A
Preparation method of composite flocculating agent
CN108585147A
Preparation method of modified nano cellulose bentonite composite material for treatment of printing and dyeing wastewater
CN109277087A
A polymer network modified bentonite and its in-situ polymerization preparation method
CN113402682B
Anionic-cationic composite intercalation type organic montmorillonite material and preparation method thereof
CN102241403A
Cited By
Desert sand ecological restoration modifier and use method thereof
CN120624030A